Role of genetics and the environment in the etiology of congenital diaphragmatichernia - Siyuan Liu; Lan Yu (BMJ Publishing Group, 2024)
Congenital diaphragmatic hernia (CDH) is a congenital malformation characterized by failure of diaphragm closure during embryonic development, leading to pulmonary hypoplasia and pulmonary hypertension, which contribute significantly to morbidity and mortality. The occurrence of CDH and pulmonary hypoplasia is theorized to result from both abnormalities in signaling pathways of smooth muscle cells in pleuroperitoneal folds and mechanical compression by abdominal organs within the chest cavity on the developing lungs. Although, the precise etiology of diaphragm maldevelopment in CDH is not fully understood, it is believed that interplay between genes and the environment contributes to its onset. Approximately 30% of patients with CDH possess chromosomal or single gene defects and these patients tend to have inferior outcomes compared with those without genetic associations. At present, approximately 150 gene variants have been linked to the occurrence of CDH. The variable expression of the CDH phenotype in the presence of a recognized genetic predisposition can be explained by an environmental effect on gene penetrance and expression. The retinoic acid pathway is thought to play an essential role in the interactions of genes and environment in CDH. However, apart from the gradually maturing retinol hypothesis, there is limited evidence implicating other environmental factors in CDH occurrence. This review aims to describe the pathogenesis of CDH by summarizing the genetic defects and potential environmental influences on CDH development.